Institutional Grammar Foundations and Applications for Institutional Analysis - Frantz, Christopher K.; Siddiki, Saba (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XV, 396 p. 145 illus., 41 illus. in color.